Empowering Mosque Committees’ Economy through Digital Technology and Eco-Friendly Architecture Implementation in Nigeria - Agoi, Moses Adeolu; Agoi, Emmanuel Taiwo; Agoi, Oluwanifemi Opeyemi; Agoi, Ayodele Elizabeth; Anas, Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The Islamic sacred architecture has been a deep expression of theological symbolism, community identity as well as socio-economic organization of the Muslim societies. In addition to the main role of worship, mosques and waqf-related religious complexes were historically multifunctional and fulfilled the roles of education, social welfare, governance, and economic redistribution. Their architectural shapes, which are marked by qiblah orientation, geometrical harmony, spatial hierarchy and connection with the environment, are products of the Islamic cosmology and ethical values that combine the spiritual piety with the social life of the day. Nonetheless, modern urban conditions characterized by the dynamic population growth, environmental pollution, and the rise of demands towards the infrastructural efficiency are changing the design, construction, and management of sacred spaces. The appearance of smart urbanization in the world and the demand of data-driven city planning and digital infrastructures are both challenges and opportunities to Islamic sacred architecture. In this dynamic environment, this community service looks at how Islamic religious architecture, especially the mosques and the use of waqf to establish religious complexes, can be redefined as part of smart city ecosystem such that they can be economically sustainable and digitally empowered. The literature review used by the study is based on a qualitative systematic literature review approach, which is based on recent peer-reviewed studies published in the period of 2020-2025 and aimed at exploring how digital technologies, including Building Information Modeling (BIM) systems, the Internet of Things (IoT), artificial intelligence (AI), and smart energy management systems, can be integrated in the design, construction, and operation of sacred buildings. The results indicate that these technologies are associated with a high level of efficiency in the operation, cost reduction in lifecycle and performance, as well as inclusion of community involvement, without losing the Islamic architectural identity and religious ethics. Moreover, the community service mentions the contribution of the Islamic social financial instruments, especially waqf and zakat, which are enhanced by digital opportunities, to the economic stability in the long run. It draws the conclusion that Islamic sacred architecture can become strong, economically efficient and spiritually significant institutions in modern smart cities when smart technologies are carefully communicated with the Islamic value system and contemporary smart cities. This is an open-access article under the CC–BY-SA license.